Blood pressure and abdominal obesity in people of the Quindio's University (Revista de Investigaciones Universidad del Quindío, 2020)
Objective. Describe two cardiovascular risk indicators (CVR), in a university population for 4 years.Material and method. A retrospective descriptive study is carried out during 4 years of blood pressure and abdominal perimeter in the university community. Variables in average, standard deviation and confidence intervals were described, a comparative analysis was made by sex; analysis of variance and Chi square were performed and a value of p
Keywords: Risk management; arterial pressure; obesity Abdominal